Relationship between objective and perceived sugar content on consumers perceptions about breakfast cereals. (March 2022) - Prada, Marília; Saraiva, Magda; Viegas, Cláudia; Cavalheiro, Bernardo P.; Vaz Garrido, Margarida
Highlights: Consumers can infer the sugar content of breakfast cereals based on FoP. Participants accurately rated the sugar content levels of products. High-sugar products were rated as tastier, fatter, and more caloric but less healthy. Perceived sugar content and frequency of consumption were negatively correlated. Abstract: In Portugal, about one-fourth of the adult population exceeds the recommended daily amount of free sugars intake. This excessive consumption may be due to a lack of awareness of the sugar content of commonly available processed products. In two studies, we explored this assumption by asking participants (convenient samples) to evaluate the sugar content of breakfast cereals based on the front-of-packaging images and analyzed the correspondence between subjective and objective sugar content. In Study 1 ( n = 90), all the exemplars were high in sugar, whereas in Study 2 ( n = 85), exemplars contained low, moderate, or high sugar content. Study 1 revealed that participants accurately perceived all exemplars as containing high sugar. Study 2 showed that participants were able to distinguish between different levels of sugar content, which impacted how they evaluated the products in other dimensions. Specifically, besides being rated as having more sugar, products with objective high (vs. moderate or low) sugar content were perceived as tastier, as having more fat and calories, but also as less healthful. Notably, participants who perceived the exemplars as containing more sugar also reported using nutritional information more often and consuming these products less frequently. These findings suggest that awareness of products' sugar content may not be sufficient to address the problem of excessive sugar intake. Intervention should also focus on building up consumers' knowledge about sugar intake guidelines and its negative health outcomes.